"Sometimes you have to pop them": Conflict and Meaning-Making in a Parenting Class. (3rd November 2020) - Cucchiara, Maia
Abstract: Parenting education is designed to address problems associated with childhood poverty, but such programs have had limited success. This ethnographic study of a parenting class serving low-income African American mothers examines tensions between parents and instructors over the use of physical force in disciplining children or in resolving conflicts more broadly. The article uses the concept of cultural frames to analyze how parents and instructors understood the issues at stake, showing significant differences between the frame the instructors used (discouraging all forms of force) and that of the parents (who saw force as sometimes necessary and effective). The instructors' therapeutic frame positioned children as vulnerable and prioritized self-esteem and positive relationships, and it did not resonate with parents, whose protective frame emphasized their responsibility to keep children safe in a dangerous world. This study examines interactions between parents and instructors to show that when frames come into conflict in social settings, collective affirmation of a particular frame can be a source of resistance and solidarity, thus raising questions about the potential of anti-poverty interventions that do not pay attention to context or meaning making.